Winter in two phases: Long‐term study of a shallow reservoir in winter. Issue 4 (28th December 2020) - Cavaliere, Emily; Baulch, Helen M.
Abstract: Climate‐driven decreases in ice‐cover duration have the potential to impact lake ecosystems, yet we have only partial understanding of the effects of winter conditions on physical, chemical, and biological properties of lakes. We used 39 years of monitoring data to examine under‐ice changes in nutrients, oxygen, and phytoplankton in a shallow drinking‐water reservoir. Two phases of winter were identified. Early winter was characterized by declining oxygen. In this phase, there were increases in specific conductance and concentrations of ammonium ( NH 4 + ‐N) and soluble reactive phosphorus (SRP). In the month prior to ice off these trends reversed themselves and phytoplankton began to increase. Specific conductance declined as meltwater entered the lake. Nutrients (SRP and NH 4 + ‐N) declined, concurrent with increases in chlorophyll a and oxygen during late winter. This work demonstrates that chemical and biotic changes through winter are highly time dependent and differ between early and late winter phases. The late winter phase is often unstudied because of unsafe ice conditions, but here, the "spring" bloom commonly occurs in late winter under ice. The phases of winter, which are likely driven by changes in light, must be considered as we work to understand how diverse lakes will respond to declining periods of ice cover, and what drives differences in the spring ecology of diverse ice‐covered lakes.